O romance dos pais, o romance dos filhos: os personagens secundários de Alejandro Zambra - Isabela Cordeiro Lopes (Caravelle)
According to the notion of « secondary characters » this paper aims to investigate the relations introduced by the narrator of the novel Formas de voltar para casa, (Ways to go back home), Alejandro Zambra, specially in contexts of family and school lives. Situated in the Post-dictatorship period, the characters who share the text’s narrative, also share the fact that they were children and teenagers during the military dictatorhip in Chili. Those « dictatorship sons » have to integrate the world , thus telling their experiences as secondary actors or leading characters as they appear in their memories and in the national memory, till they make sense. It’s the way this process is shown in the fiction that represents the book’s main interest, shown by thoroughly reading and analysing the roles played by each character.